Understanding the TPACK Framework Among Technical Students: Evidence from Civil Engineering and Planning at UNM - Muhammad Haristo Rahman; Mudarris; Akmal Hidayat (Information Technology Education Journal, 2025)
In an era of digital transformation, the integration of technology in education has become indispensable—especially in technical disciplines such as civil engineering. This study explores how students in the Civil Engineering and Planning program at Universitas Negeri Makassar perceive their competence within the Technological Pedagogical and Content Knowledge (TPACK) framework. Utilizing a quantitative descriptive design, a structured survey was administered to 75 students to assess their self-reported proficiency in the domains of technological, pedagogical, and content knowledge. The results indicate strong confidence in the use of technology for content comprehension and problem-solving, while moderate scores were observed in pedagogical and integrative dimensions of TPACK. These findings reveal both strengths and gaps in students’ readiness to apply TPACK holistically, highlighting the need for curriculum innovation that balances technical fluency with pedagogical strategy. The study extends the application of the TPACK framework beyond teacher education, offering insights for advancing instructional competence in engineering education. Recommendations for future research include triangulated methods, longitudinal studies, and cross-disciplinary comparisons to enrich understanding of TPACK adoption in higher technical education.